2020
DOI: 10.1039/c9ob02587a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and mechanistic aspects of sulfonyl migrations

Abstract: Sulfonyl migrations, frequently described as ‘unusual’ or ‘unexpected’, from the last 20 years, including 1,2-, 1,3-, 1,4-, 1,5-, 1,6- and 1,7-sulfonyl shifts, through either radical or polar processes, either inter- or intramolecularly are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 170 publications
0
26
0
Order By: Relevance
“…Initially, the α-position of sulfonyl group would undergo lithiation upon treatment with LDA to deliver A and then a 4-exo-dig cyclization would occur to generate four-membered β-sultam intermediate B 63 , 64 , 67 , 68 . Subsequently, B presumably undergoes a 1,3-sulfonyl migration to form lithium thiete sulfone intermediate C 69 , 70 , which could be protonated by MeOH to deliver product 2 . When MeOH was replaced by other electrophilic reagents, intermediate C could be functionalized directly to obtain N -substituted thiete sulfone products.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the α-position of sulfonyl group would undergo lithiation upon treatment with LDA to deliver A and then a 4-exo-dig cyclization would occur to generate four-membered β-sultam intermediate B 63 , 64 , 67 , 68 . Subsequently, B presumably undergoes a 1,3-sulfonyl migration to form lithium thiete sulfone intermediate C 69 , 70 , which could be protonated by MeOH to deliver product 2 . When MeOH was replaced by other electrophilic reagents, intermediate C could be functionalized directly to obtain N -substituted thiete sulfone products.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our ongoing studies to develop catalytic reactions, [1] we recently reported that an oxa‐ and azacycle‐forming reaction of sulfonylalkynols and sulfonylalkynamides was triggered by nucleophiles, such as an N‐heterocyclic carbene (NHC), [2] 4‐dimethylaminopyridine (DMAP), and phosphines (Scheme 1). [3] In the presence of catalytic amounts of these nucleophiles, bond formation with the internal O‐ or N‐nucleophile occurred at the γ‐position of sulfone with 1,2‐sulfonyl migration [4,5] . This transformation can be regarded as an example of γ‐umpolung bond formation because the latent polarity of the γ‐position is negative [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…[3] In the presence of catalytic amounts of these nucleophiles, bond formation with the internal O-or N-nucleophile occurred at the γ-position of sulfone with 1,2-sulfonyl migration. [4,5] This transformation can be regarded as an example of γ-umpolung bond formation because the latent polarity of the γ-position is negative. [6,7] We proposed the following mechanism: (1) Tautomerization of propargyl sulfone 1 occurs to generate sulfonylallene I.…”
Section: Introductionmentioning
confidence: 99%
“…Benzaldehyde goes through a successive nucleophilic attack, leading to the formation of the by-product 4a. 1,2-Sulfonyl migration 20 of intermediate C gives rise to intermediate D, which immediately undergoes protonation to furnish the desired product N-sulfonylformamidine 3a.…”
mentioning
confidence: 99%